Kebudayaan Indis: Hasil Akulturasi Budaya antara Jawa dengan Kolonial Belanda - Wahyu Agil Permana; Andini Shira Putri; Rinaldo Adi Pratama (Journal Social and Humaniora, 2023)
Indische culture is a culture that results from a combination of European (Dutch) culture and local (Javanese) culture. Starting from the arrival of the Dutch to Indonesia which resulted in a cultural contact. Caused by this cultural contact, then led to acculturation between Dutch culture and local culture resulting in a new culture called Indische culture. This article was written with the aim of finding out about how Indische culture can enter and develop in Indonesia. The method used is literature study, namely by collecting historical sources and data consisting of archives, documents, books, journals, newspapers and magazines.